Wykroczenia przeciw mieniu na przykładzie Prawa o wykroczeniach z 1932 roku w świetle orzecznictwa Sądu Najwyższego - Pasek, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article presents a dispute over the model of codification of misdemeanor law in Poland in the interwar period in the Criminal Law Section of the Codification Commission. It indicates that the 1932 misdemeanor law was a compromise solution, covering the most common misdemeanors, subjected in the first instance to the jurisdiction of authorized administrative bodies. Its Chapter VI covered offenses against property. They had a modern, synthetic character. Using them as an example, the role of the Supreme Court’s jurisprudence in correctly qualifying the perpetrator’s behavior as either a misdemeanor or a misdemeanor against property from the Criminal Code was demonstrated. This is because the Supreme Court assessed in cassation proceedings whether the perpetrator’s behavior exhausted the elements described in Articles 54–63 of the Misdemeanor Law or fell under the relevant provision of the Penal Code.
Keywords: criminal law; offenses; case law; Supreme Court